La théâtralité du tableau vivant dans le théâtre de Samuel Beckett: une perspective néo-avant-gardiste - POP-CURŞEU, Ştefana (Studia Universitatis Babeș-Bolyai Dramatica, 2017)
The theatricality of the living pictures in Samuel Beckett’s theatre: a Neo-Avant-guard perspective. Samuel Beckett’s theatrical work has been quite often compared, especially in the recent literature, to the abstract directions in modern painting and sculpture, but there was no attempt to analyse its relationship to its contemporary artistic movements taking their roots in the historical Avant-guards. The present article proposes to revisit Samuel Beckett’s theatre through a new perspective, mainly that of the theatricality of the living pictures (tableaux vivants) present in his stage conception, through the bias of European and American Pop Art, Assemblagism, New Realism and other Neo-Avant-guard artistic movements. Reconsidering thus an essential moment of theatre history, with the instruments of theatre iconography, we try to open new doors in the understanding of his work as a playwright and as a stage director, by replacing it in the right context of visual and performing arts.